Assessment of Patients’ Future Outlook after Bowel Resection in Crohn’s Disease - Shasha Tang; Xiaolong Ge; Weilin Qi; Wei Liu; Qian Cao; Wei Zhou (Gastroenterology Research and Practice)
Background. Many patients with Crohn’s disease (CD) require surgery in their life. Their future outlook is crucial to psychological and mental health after surgery. This study is aimed at assessing CD patient’s outlook after experiencing bowel resection and determining factors associated with patient’s outlook. Methods. We used an ad hoc questionnaire (modified WHOQOL-BREF) to assess patients’ outlook for the future after bowel resection in CD. All patients who experienced bowel resection for CD from 2015 to 2017 were included in this study. Patients were divided into two groups according to the questionnaire. Patients who had a positive outlook were compared with those who had a negative outlook. The patients’ view on timing of surgery was also recorded. Results. Of 114 eligible patients surveyed, 103 (90.4%) responded. 65 (63.1%) reported that the timing of surgery was appropriate, and 26 patients felt it should have been performed earlier, while remaining 12 preferred a later surgery. 61 (59.2%) patients had a positive outlook of their future lives, while 42 patients had a negative outlook. Factors as the financial burden, employment status, patients’ view on timing of surgery, and clinical recurrence were associated with patients’ outlook. In the multivariate analysis, only clinical recurrence was an independent risk factor for patient’s future outlook. Conclusion. From this survey, it is clear that most patients who underwent an elective bowel resection for CD are satisfied with their timing of surgery. Patients who have clinical recurrence carry a significant negative outlook for their future life. Postoperative management which focuses on preventing clinical recurrence may enhance patients’ outlook for the future.